Potential of the marine diatom Halamphora coffeaeformis to simultaneously produce omega-3 fatty acids, chrysolaminarin and fucoxanthin in a raceway pond - Popovich, Cecilia (2020)
Omega-3 eicosapentaenoic fatty acid (C20:5; EPA), β-glucan and fucoxanthin have received widespread attention owing to their potential industrial applications; however, their availability is currently limited to unsustainable sources such as fish oils and macroalgae. Though some species of diatoms are also a natural source of these metabolites, progress needs to be made in reducing the cost barriers involved in their large-scale production. The aim of the present study was therefore to assess the potential of the marine diatom Halamphora coffeaeformis to simultaneously accumulate EPA, chrysolaminarin and fucoxanthin in a raceway pond sustained by fertilizer (Bayfolan®)-enriched seawater. The biomass production increased significantly along the experiment, the specific growth rate, biomass productivity and areal yield being 2.03 day−1, 0.128 g.L−1.d−1 and 25.73 g.m−2.d−1, respectively. Proteins dominated in the first culture phase, while lipids, carbohydrates and pigments increased toward the end of the stationary phase. The harvested biomass presented 310 mg.g−1 DW (dry weight) of total lipids containing high amounts of EPA (24% of total fatty acids), 114 mg.g−1 DW of chrysolaminarin and 38 mg.g−1 DW of fucoxanthin. These values compare favorably with those obtained from commercially used sources. The culture medium proposed represents a non-conventional, cost-effective resource allowing for sustained high biomass levels throughout 22 days, guaranteeing the accumulation of valuable metabolites. Furthermore, the robustness and auto-flocculation capacity of the species increase the chances of viable scalability. These findings indicate the potential of H.coffeaeformis as a high-value metabolite feedstock, focusing on sustainable bioprocesses.